Effectiveness of acupuncture therapy as treatment for tinnitus: a randomized controlled trial - Doi,Marcelo Yugi (2016)
ABSTRACT INTRODUCTION: Tinnitus is a subjective sensation of hearing a sound in the absence of an external stimulus, which significantly worsens the quality of life in 15-25% of affected individuals. OBJECTIVE: To assess the effectiveness of acupuncture therapy for tinnitus. METHODS: Randomized clinical trial (REBEC: 2T9T7Q) with 50 participants with tinnitus, divided into two groups: 25 participants in the acupuncture group and 25 participants in the control group. The acupuncture group received acupuncture treatment and the control group received no treatment. After a period of 5 weeks, they were called to perform the final evaluation and the control group received acupuncture treatment for ethical reasons. RESULTS: A statistically significant result was found for the primary outcome, reducing the intensity of tinnitus, with p = 0.0001 and the secondary endpoint, showing improvement in quality of life, with p = 0.0001. CONCLUSION: Chinese scalp acupuncture associated with bilateral electroacupuncture demonstrated, in the short term, a statistically significant improvement by reducing the level of tinnitus intensity, as well as improving the quality of life of individuals with tinnitus.